China Satellite Navigation Conference (CSNC) 2018 Proceedings Volume I (Lecture Notes in Electrical Engineering,, 2018)
These proceedings present selected research papers from CSNC 2018, held during 23rd-25th May in Harbin, China. The theme of CSNC 2018 is Location, Time of Augmentation. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou System (BDS) especially. They are divided into 12 topics to match the corresponding sessions in CSNC 2018, which broadly covered key topics in GNSS. Readers can learn about the BDS and keep abreast of the latest advances in GNSS techniques and applications.